Investigation of changes in Hematological parameters and levels of Oxidative stress factors in castrated Cats - Polat, Eren; Acisu, Tutku Can; Sonmez, Mustafa; Unsaldi, Emine; Otlu, Önder; Tanrisever, Murat; Baykalir, Yasin (Univ Zulia, Facultad Ciencias Veterinarias, 2023)
This study was carried out to determine the effect of castration procedure on hemogram and leukogram values and the levels of oxidative stress factors in serum tissue in cats. Preoperative and postoperative 10th day hemogram/leukogram values and total oxidant/antioxidant capacities of 19 castrated cats were evaluated in the study. When the hemogram and leukogram values were examined, it was determined that there was a statistically significant increase in the amount of eosinophils (P<0.05). Although the increase in white blood cells (WBC), neutrophil and lymphocyte levels and the decrease in red blood cells (RBC) and hematocrit (HCT) levels were remarkable, it was not found to be statistically significant (P>0.05). When the levels of oxidative stress factors in the serum tissues of the cats were examined, it was determined that there was a decrease in the total antioxidant status (TAS) and an increase in the total oxidant status (TOS), but the difference in the results was not statistically significant (P>0.05). In conclusion, in this study, it was determined that the castration procedure in cats did not cause a significant difference in hemogram and leukogram parameters and the level of oxidative stress factors in serum tissue, except for the amount of eosinophils.
Investigación de cambios en parámetros hematológicos y niveles de factores de estrés oxidativo en gatos castrados
Keywords: Castration; cat; eosinophil; hemogram; oxidative stress